1999
DOI: 10.1105/tpc.11.12.2365
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the D1 Precursor in Monomeric Photosystem II Reaction Center Precomplexes Precedes Chlorophyll a–Triggered Accumulation of Reaction Center II in Barley Etioplasts

Abstract: Assembly of plastid-encoded chlorophyll binding proteins of photosystem II (PSII) was studied in etiolated barley seedlings and isolated etioplasts and either the absence or presence of de novo chlorophyll synthesis. De novo assembly of reaction center complexes in etioplasts was characterized by immunological analysis of protein complexes solubilized from inner etioplast membranes and separated in sucrose density gradients. Previously characterized membrane protein complexes from chloroplasts were utilized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…When PSII is rendered inoperable, the PSII center migrates from the grana to the stroma lamellae where the damaged D1 is removed and the new protein inserted (Choquet and Vallon 2000). Studies of D1 synthesis in intact chloroplast translation systems (Zhang et al 1999) have demonstrated that D1 associates with a D2-cytochrome b559 complex during translation (Adir et al 1990;van Wijk et al 1997;Muller and Eichacker 1999;Zhang et al 1999), which is thought to stabilize the nascent protein. A previous study by Salonen et al (1998) also observed a decrease in the turnover of D1 in leaf discs of chilling-sensitive pumpkin exposed to low temperature and high light.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When PSII is rendered inoperable, the PSII center migrates from the grana to the stroma lamellae where the damaged D1 is removed and the new protein inserted (Choquet and Vallon 2000). Studies of D1 synthesis in intact chloroplast translation systems (Zhang et al 1999) have demonstrated that D1 associates with a D2-cytochrome b559 complex during translation (Adir et al 1990;van Wijk et al 1997;Muller and Eichacker 1999;Zhang et al 1999), which is thought to stabilize the nascent protein. A previous study by Salonen et al (1998) also observed a decrease in the turnover of D1 in leaf discs of chilling-sensitive pumpkin exposed to low temperature and high light.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in Chlamydomonas reinhardtii identified initiation of translation as a main regulatory step in the biogenesis of the core proteins D1 and apoCP47 (Minai et al 2006). Repair of photodamaged reaction centers, however, is most likely regulated at elongation of translation (Kim et al 1994;Kettunen et al 1997;Minai et al 2006) as the reaction center core must be partially disassembled to allow the cotranslational insertion of D1 (Adir et al 1990;van Wijk et al 1997;Muller and Eichacker 1999;Zhang et al 1999). Cotranslational insertion explains why D1 is not found free in the membrane and is typically associated with at least D2 (Zhang et al 1999).…”
mentioning
confidence: 97%
“…In case of PSII photoinhibition, Cyt b 559 is degraded in parallel with the rest of the PSII reaction center [46]. However, free Cyt b 559 has for instance been observed in etioplasts prior to PSII assembly during de-etiolation [47,48] or in a screen for HCF mutants, particularly those affected in PSII [33]. It has recently been proposed that Cyt b 559 acts as a plastoquinole oxidase [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the proteins in the photosynthetic machinery, e.g. Hcf136 and the oxygenevolving complex, are of importance already at an early stage of chloroplast development, because of their roles in the correct assembly of the photosystems (Ryrie et al 1984;Hashimoto et al 1993;Müller and Eichacker 1999;Plücken et al 2002). The presence of chlorophyll is a prerequisite for the accumulation of most chlorophyll-binding proteins, e.g.…”
Section: Thylakoid Proteins As Components Of Plbsmentioning
confidence: 98%